Effects of Temperature in Different Initial Duration Time for Soft Clay Stabilized by Fly Ash Based Geopolymer - Abdalla Mohammed Shihab; Jasim M Abbas; Amer M Ibrahim (Salehan Institute of Higher Education, 2018)
When soft clay soils are included in engineering projects, it’s stabilized usually with some kinds of admixtures named as stabilizers. The common stabilizers that highly practiced are OPC, lime, high calcium fly ash (FA), etc. Each one of these stabilizers has its shortcomings. Geopolymers are the product of alkali activated aluminosilicate sources that excelled as an alternative to ordinary binders due to its sustainability, low cost and good mechanical properties. This study investigates the effects of some key elements like liquid over fly ash ratio (Liq/FA), initial duration curing time (D) and its temperature to soil – FA based Geopolymers samples characterized by its unconfined compressive strength testing (UCS), volumetric measurements, scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and X-Ray diffraction (XRD). The Liq/FA taken as 2.71, 3.167, 3.8 and 4.75 respectively and the duration time taken were 1, 6, 18 and 24 hrs. respectively. The tests results showed that the maximum peak strength gain when Liq/FA is 3.8 at 90 oC with 24 hrs. D. It was observed that Young’s Modulus increased with increasing curing temperature for certain D. Volumetric strain increased by increasing D and its temperature. SEM and XRD analyses confirmed the Geopolymers gels formation for a selective precursor while EDX analyses showed that silicon over aluminium ratio is 1.38 for selective spectrum within the gel to the same mixture.